The Construction of Biden’s Tendency Towards The War Between Russia and Ukraine by CNN Online News - Mohammad Syahidan (Fakultas Ilmu Budaya, 2024)
The topic of Biden’s tendency is one of the issues that were part of the news about the war between Russia and Ukraine recorded by CNN news media. The construction of Biden’s tendency produced by CNN triggers an idea about the possible appearance of manipulation towards the news reader’s mind. This research aims to discover the possibility of the news of Biden’s tendency to influence the news reader’s social cognition and lead to mind control due to the use of language features in the news text. This research is qualitative, where the data comes from the news documents. This research uses Critical Discourse Analysis (CDA) by van Dijk, known as the Socio-Cognitive Approach (SCA), as the theoretical approach to analyze the text. This approach is combined with several approaches in line with the SCA’s dimension consisting of structural text analysis that are macrostructure, superstructure, and microstructure from van Dijk, social cognition approach from Fiske and Taylor, and Context of situation and culture from Halliday and Hasan. These approaches produce the idea that the news text used to deliver the information regarding Biden’s tendency towards the war between Russia and Ukraine is a persuasive discourse. Persuasive discourse is constructed through rhetorical words packaged in the construction of reason to support the construction of Biden’s tendency. The journalists’ social cognition also plays a significant role in the process of news construction to achieve the purpose of persuasive discourse. The placement of the construction reason done by the journalists is assumed to be the tool for the context models for the news reader. With the placement of text construction in such a way, the context model that the newsreader got is expected to be linear with the idea brought by the news text where the position of Biden is upheld as a tolerant person who cares for human rights.
Reupload file repositori 11 Mar 2026_Maya